Going with, then against the flow: evidence against the optomotor hypothesis of fish rheotaxis. (September 2015) - Bak-Coleman, Joseph; Smith, Derek; Coombs, Sheryl
Abstract : Movement through an environment provides sighted organisms with dynamic visual cues known as optic flow. In flying insects, optic flow is important for collision avoidance, flight speed control and landing manoeuvres. The function of optic flow is much less understood in other taxa, particularly in fish. Despite a lack of quantitative studies, optomotor responses (OMRs) to optic flow are presumed to be nearly ubiquitously important for rheotaxis (orientation to currents), a widespread behaviour that confers a number of benefits, including energy conservation. Here we show that while very young larval zebrafish, Danio rerio, exhibit positive OMRs (swim in the direction of optic flow), thereby minimizing optic flow on the retina, older larvae and adults exhibit negative OMRs that increase optic flow. While the reason for this reversal remains unclear, negative OMRs are inconsistent with optically driven positive rheotaxis (orienting upstream). Furthermore, when optic flow cues are placed in conflict with nonvisual (mechanical) cues generated by water currents, adult fish largely ignore the optic flow cues relying instead on nonvisual cues. These results challenge a century-old belief that optic flow and the resulting OMRs are a dominant sensorimotor mechanism in rheotaxis, highlighting the importance of future work on life history changes in OMRs and the possible modulatory influence of learned, multisensory expectations. Highlights: We tested assumptions and predictions of the optomotor hypothesis of rheotaxis in zebrafish. Adults showed weak, negative optomotor responses (OMRs) to optic flow alone. Optic flow yaw and slip illusions failed to disrupt rheotaxis in adults. OMRs changed from positive to negative early in life (16–18 days postfertilization). Rheotaxis in larval and adult zebrafish cannot be consistently explained by OMRs.